FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON KEUANGAN DI INDONESIA - Angelica, Martha; Prajitno, Sugiarto (E-Jurnal Akuntansi TSM, 2023)
This study aims to determine the effect of the dependent variable Firm Value on the independent variables’ Return On Assets, Debt to Asset Ratio, Current Assets, Firm Size, Dividend Payout Ratio, Sales Growth, and Tax Avoidance. The object of this study uses data from non-financial companies listed on the Indonesia Stock Exchange from 2019-2021 as the population. The sampling process used the purposive sampling method and the method for analyzing data used the multiple regression method. There were 79 companies, with 237 data that passed the criteria. This study states that Return On Assets, Debt to Asset Ratio, and Tax Avoidance has an effect on Firm Value but Current Ratio, Firm Size, Dividend Payout Ratio, and Sales Growth have no effect on Firm Value.